Clinical Manifestations of Hemochromatosis in HFE C282Y Homozygotes Identified by Screening - Gordon D McLaren; Christine E McLaren; Paul C Adams; James C Barton; David M Reboussin; Victor R Gordeuk; Ronald T Acton; Emily L Harris; Mark R Speechley; Phyliss Sholinsky; Fitzroy W Dawkins; Beverly M Snively; et al. (Canadian Journal of Gastroenterology)
BACKGROUND: Patients with hemochromatosis may suffer organ damage from iron overload, often with serious clinical consequences.